Pulsed radiofrequency on the occipital nerve for treatment of short-lasting unilateral neuralgiform headache: A case report - Fatima López Gonzalez; Isabel Beltrán Blasco; Cesar Margarit Ferri (SAGE Publishing, 2020)
Short-lasting unilateral neuralgiform headache (Short-lasting Unilateral Neuralgiform headache attacks with Conjunctival injection and Tearing (SUNCT)/Short-lasting Unilateral Neuralgiform headache attacks with Autonomic Symptoms) is a trigeminal autonomic cephalalgia with difficult treatment and its management is based on neuromodulator drugs and sometimes ablative procedures on the trigeminal nerve. A positive response to occipital anesthetic blocks and peripheral and deep neurostimulation has also been described. We present the case of a patient with criteria of left SUNCT and transient response to occipital anesthetic blocks, satisfactorily controlled with pulsed radiofrequency (PRF) of the occipital nerve. Upon examination, the patient had tenderness in the left greater occipital nerve (GON). Blockade was performed with anesthetic and corticosteroid, obtaining a highly positive but transient response. After several nerve blocks, the patient was referred to the Pain Unit where pulsed radiofrequency on the left GON was performed. After two sessions, more than 90% of reduction of pain was achieved, maintained for 12 months. There haven't been found data in the literature on the use of GON PRF for the treatment of SUNCT, while there are descriptions for other types of cranial pain. The intention of our case is to make this procedure to be considered as an alternative for the treatment of this entity in patients who respond to anesthetic blocks.